Developing a fuzzy model for Tehran's air quality - Nafiseh Tokhmehchi; Ahmad Makui (Management Science Letters)
This research aims to offer a fuzzy approach for calculating Tehran's air pollution index. The method is based on fuzzy analysis model, and uses the information about air quality index (AQI), included on the website of Tehran’s Air Quality Monitoring And Supervision Bureau. The contrived fuzzy logic is considered a powerful tool for demonstrating the information associated with uncertainty. In the end, several graphs visualize this inferential system in various levels of pollution.